Effects of treatment time and temperature on the DC corona pretreatment performance of waste activated sludge - 高宇;赵宁;邓永迪;王明行;杜伯学 (Plasma science & technology, 2018)
In order to improve the anaerobic digestion efficiency of waste activated sludge（WAS）,a pretreatment procedure should be carried out so as to disrupt the microbial cell structure,thus releasing intracellular organic matters.In this paper,a corona discharge triggered by a DC voltage was employed to pre-treat WAS for various time periods under different temperatures.The magnitude of the DC voltage was 4 k V at both negative and positive polarities.The changes in the soluble chemical oxygen demand,phosphorus and nitrogen content,and p H value within the WAS were utilized to estimate the pretreatment performance of the DC corona.It was found that with increasing treatment time,the pretreatment efficiency tends to be reduced.With increased temperature,the pretreatment efficiency appears to be better.It is suggested that the oxidative species and the active particles generated in the corona discharge play an important role in disrupting the microbial cell structure,which is dependent upon the treatment time and the temperature.